Efforts to Control Potential Hazards of Working at Height at a Gresik Fertilizer Company, Indonesia - Dana Aprilia; Aziz Ramadhan (Universitas Airlangga, 2021)
Introduction: As one of the largest fertilizer industrieswith high competitiveness and high interest from consumers, the Gresik Fertilizer Company has various potential hazards that can cause workplace accidents, one of which is the danger of working at height. This study aims to determine the Occupational Safety and Health (OSH) programs and the application of hazard control of working at height in the Gresik Fertilizer Company. Methods: This study used a descriptive analysis method with a cross sectional study design. The variables studied were the hazard control efforts, the procedures to control the hazard, and the application of the hazard control process of working at height. Data collection techniques derived from secondary data in the form of company’s documents, and the data analysis method used in this study was in the form of qualitative method. Results: the Gresik Fertilizer Company has several OSH programs for the control of hazard of working at height with a success rate of 90%, have control methods of working at height with a success rate of 90%, and have guidelines for working at height with a success rate of 85%. Conclusion: The Gresik fertilizer company has OSH programs to control working at height, has hazard control methods for working at height, and guidelines for working at height.Keywords: control efforts, fertilizer company, working at height hazards